1977
DOI: 10.1111/j.1399-3054.1977.tb04049.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Mercury Chloride by Chlorella: Evidence for a Reducing Factor

Abstract: Evidence is brought for the presence of low molecular weight, heat stable, mercury reducing factors in Chlorella cells. Some of the properties of these factors, which appears to be normal metabolities, are described. These factors are also present in the medium in which the cells grow. The reduced mercury, Hg0, is volatilized from the culture medium more rapidly than Hg+2. The resultant decrease in the Hg concentration appears to be the main reason for the recovery of the cells from Hg stress. No resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…In contrast, so far, few studies report the formation of Hg° in phytoplanktonic algae (Ben-Bassat and Mayer, 1977;Mason 1995;Devars et al, 2000) and, in addition, this reduction mechanism is largely unknown. It is well known that elemental mercury (Hg°) plays a fundamental role in the biogeochemical cycle of mercury (Schroeder et al, 1989;Horvat et al, 2003) since it constitutes 90% of volatile forms of mercury in natural waters, named Dissolved Gaseous Mercury (DGM).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, so far, few studies report the formation of Hg° in phytoplanktonic algae (Ben-Bassat and Mayer, 1977;Mason 1995;Devars et al, 2000) and, in addition, this reduction mechanism is largely unknown. It is well known that elemental mercury (Hg°) plays a fundamental role in the biogeochemical cycle of mercury (Schroeder et al, 1989;Horvat et al, 2003) since it constitutes 90% of volatile forms of mercury in natural waters, named Dissolved Gaseous Mercury (DGM).…”
Section: Introductionmentioning
confidence: 91%
“…Hg° production could involve cell surface reduction, similar to that found for other trace metals (Jones et al, 1987) rather than a gene encoded Hg resistance mechanism, as in the case of prokaryotic microorganisms. Ben-Bassat and Mayer (1977) isolated from crude extracts of the green alga C. pyrenoidosa an intracellular fraction (molecular weight < 1200 Da) responsible for Hg reduction, but its nature remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, between 2 and 20 mg L −1 have been used in experiments with poplar plantlets and with extracted algal cells (Rugh et al . 1998; Ben‐Bassat & Mayer 1977), and up to 12 mg kg −1 soil in controlled‐environment exposure of aspen (Ericksen & Gustin 2004). Even if these concentrations are below those on Hg‐contaminated sites (Millan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The genuine metabolic reduction of Hg(II) by plants can therefore be investigated only in the absence of bacterial processes which is hardly feasible for plants in situ . The reduction has been investigated to some extent for cultivated algal cells, yet without identifying the mechanism (Ben‐Bassat & Mayer 1977, 1978). For terrestrial plants, however, an active detoxification has hitherto not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies further suggest that methanotrophs may play a role in controlling Hg transformation such as MeHg degradation (Vorobev et al ; Lu et al ). Hg(II) reduction can also be carried out by eukaryotic phytoplankton (Ben‐Bassat and Mayer ; Mason et al ), but the mechanism of this pathway is not well understood or is often overlooked. Recent studies showed that phototrophic microorganisms (bacteria and algae) can use Hg(II) as an electron sink to maintain intracellular redox homeostasis, producing Hg 0 and therefore modifying the availability of Hg to methylation sites (Grégoire and Poulain , ).…”
mentioning
confidence: 99%